Teaching residents mental health care. Issue 12 (December 2018) - Smith, Robert C.; Laird-Fick, Heather; Dwamena, Francesca C.; Freilich, Laura; Mavis, Brian; Grayson-Sneed, Katelyn; D'Mello, Dale; Spoolstra, Mark; Solomon, David
Highlights: 85% of mental health care is provided by (untrained) medical physicians. Teaching medical faculty to train residents in mental health care is effective. This avoids the current impasse of too few psychiatrists to teach in medicine. Abstract: Objective: We tested the hypothesis that trained medical faculty can train residents effectively in a mental health care model. Methods: After the authors trained medical faculty intensively for 15 months in primary care mental health, the newly trained faculty taught medical residents intensively. Residents were evaluated pre- and post-residency and compared to non-equivalent control residents in another city. Using ANOVA, the primary endpoint was residents' use of a mental health care model with simulated patients. Secondary endpoints were residents' skills using models for patient-centered interviewing and for informing and motivating patients. Results: For the mental health care model, there was a significant interaction between study site and time (F = 33.51, p < .001, Eta 2 = .34); mean pre-test and post-test control group scores were 8.15 and 8.79, respectively, compared to 7.44 and 15.0 for the intervention group. Findings were similarly positive for models of patient-centered interviewing and informing and motivating. Conclusions: Training medical faculty to teach residents a mental health care model offers a new educational approach to the widespread problem of poor mental health care. Practice Implications: While the models tested here can provide guidance in conducting mental health care, further evaluation of the train-the-trainer program for preparing residents is needed.